The Role of Silicate in the Parasitism of Pleurosigma sp. Diatoms by the Thraustochytrid Phycophthorum isakeiti - Powers, Daniel Jerome Finley (UiT The Arctic University of Norway, 2020)
The recently described thraustochytrid diatom parasite Phycophthorum isakeiti has been isolated from the marine system of northern Norway (Hassett, 2020). Protist P. isakeiti’s ecological role, biodiscovery potential, and interactions with a possible diatom host, Pleurosigma sp. remain largely unexplored. Here I present culturing experiments to test whether P. isakeiti is an obligate parasite. To supplement this analysis, incidence of infection and division was explored in a P. isakeiti-Pleurosigma sp. model system and assessed as a function of time in the presence of standard and reduced silicate conditions. Nutrient analysis and cell counting experiments spanning 15 to 31 days were conducted to investigate rates of free silicate uptake, free nitrate uptake, and the effect of P. isakeiti on rates of Pleurosigma sp. division and infection. Resin and ethyl acetate extractions were performed to characterize and screen for allelopathic chemicals involved in diatom defense or thraustochytrid parasitism. Lastly, bioassays were undertaken to detect whether any primary or secondary metabolites produced during host parasitism had biotechnologically relevant activities. Contrary to my hypothesis that P. isakeiti would be able to grow in the absence of its diatom host due to its presence in highly seasonal, light limited climates like northern Norway, I found no evidence to support a facultative strategy of P. isakeiti in a variety of tested medium. In coculturing experiments, the proportion of host Pleurosigma sp. cells dividing increased over time in the presence of the parasite, P. isakeiti. The silicate was depleted in media to a greater extent in parasitized cultures compared to non-parasitized cultures suggesting greater uptake of silicate in parasitized diatom populations. Two compounds, C17H27NO2 (4.2422 min; 278.20923 m/z) and C23H16O2 (9.2357min, 325.12084 m/z), were detected through liquid chromatography mass spectrophotometry exclusively in Pleurosigma sp. cultures parasitized by P. isakeiti. Limited ...